MICRO-ENTERPRISE RESILIENCE COWHIDE CRACKERS "RSD": STRATEGIES TO INCREASE BUSINESS CAPACITY - Worogati Worogati; Bambang Dwi Suseno (International Journal of Engagement and Empowerment, 2022)
This study aimed to learn more about making and analyzing the economics of cowhide crackers made at the small business center "RSD" in Unyur Village, Serang City. In the small business center of cowhide crackers, "RSD," case study techniques are applied. All methods and stages of making cowhide crackers are observed to determine the production process. Soaking raw materials, tapping, burning fur, boiling, draining, scraping hair, cutting, drying I, seasoning, drying II, frying I, frying II, and packing are all phases in the production of cowhide crackers. For the sales and marketing process, economic analysis is carried out by determining all costs incurred during the manufacture of cowhide crackers. According to details of the labor and production system of the "RSD" leather cracker business, ten personnel are employed in this industry. The processing time was 480 minutes (8 hours), the production goal was 1,200 packs, and the overall overall overall result was 1,000 packs